Quantification of mitochondrial DNA from peripheral tissues: Limitations in predicting the severity of neurometabolic disorders and proposal of a novel diagnostic test. (February 2020) - Chinopoulos, Christos
Abstract: Neurometabolic disorders stem from errors in metabolic processes yielding a neurological phenotype. A subset of those disorders encompasses mitochondrial abnormalities partially due to mitochondrial DNA (mtDNA) depletion. mtDNA depletion can be attributed to inheritance, spontaneous mutations or acquired from drug-related toxicities. In the armamentarium of diagnostic procedures, mtDNA quantification is a standard for disease classification. However, alterations in mtDNA obtained from peripheral tissues such as skin fibroblasts and blood cells do not often reflect the severity of the affected organ, in this case, the brain. The purpose of this review is to highlight the pitfalls of quantitating mtDNA from peripheral –and not limited to-tissues for diagnosing patients suffering from a variety of mtDNA depletion syndromes exhibiting neurologic abnormalities. In lieu, a qualitative test of mitochondrial substrate-level phosphorylation –even from peripheral tissues-reflecting the ability of mitochondria to rely on glutaminolysis in the presence of respiratory chain defects is proposed as a novel diagnostic assessment of mitochondrial functionality.